Micro‐Mesopores Nitrogen‐Doped Carbon Combined Polar‐MoS2 as Host for High‐Performance Li‐S Batteries. Issue 10 (12th March 2020) - Zhao, Liping; Liu, Gang; Xu, Shuoyan; Zhao, Ye; Wang, Ya; Li, Dan; Fu, Fang; Zheng, Yue; Xie, Haiming; Zhang, Peng
Abstract: A composite of MoS2 /MMNC (micro‐mesopores nitrogen‐doped carbon) was prepared through a simple hydrothermal method and utilized as a host for Li−S battery. The crystal structure of MoS2 /MMNC−S composite were tested by X‐ray diffraction (XRD), Raman Spectroscopy and X‐ray photoelectron spectroscopy (XPS). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to characterize its morphology. The pore size distribution and weight ratio of sulfur were measured via N2 adsorption‐desorption isotherm and thermogravimetric analysis (TGA), respectively. MoS2 /MMNC−S composite showed a good electrochemical performance as the positive electrode for Li−S battery. The rate performance of the battery is ideal and the capacity retention is maintained at ∼ 90% after 200 cycles at 0.5 C. Abstract : Micro‐mesopores nitrogen‐doped carbon polar material MoS2 /MMNC−S‐x was prepared. The physical properties indicate that MoS2 /MMNC−S‐x composites have high surface area, broad range of pore‐size, and large amount of sulfur. As positive electrodes of Li−S batteries, MoS2 /MMNC−S‐x composites exhibit high specific capacity, high rate performance and extended life of cycle. The composite has great potential as electrode material of Li−S batteries yielding high energy density and long life time.